Studi Semiotika Makna Upacara Perayaan Dewi Kwan Im di Kelenteng Dewi Kwan Im Palembang - Jessica Gunawan; Suzy Azeharie (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2021)
This research discusses of rituals for Dewi Kwan Im celebration that is the day Dewi Kwan Im leaving the world. Dewi Kwan Im is the Goddess who was highly respected by Khonghucu people’s because Dewi Kwan Im trusted can be helps Khonghucu people’s who need helps. Therefore Khonghucu people’s always celebrate the biggest day of Dewi Kwan Im. Dewi Kwan Im Temple where located at KM 12 Palembang also held a celebration ceremony in welcoming the great day of Dewi Kwan Im with has its own rituals tradition in carrying out the celebration ceremony of Dewi Kwan Im. Every rituals procession which help held in Dewi Kwan Im Palembang Temple has a meaning in it. The purpose of this research is to know the meaning of rituals celebration for Dewi Kwan Im at Dewi Kwan Im Temple Palembang and to know the tradition which did by the Khonghucu people’s at Dewi Kwan Im Temple Palembang in celebrating the rituals of Dewi Kwan Im. The theories which used in this research are semiotics theory, transcendental communication theory and assimilation theory. The research methods that used is qualitative research methods with a case study approach. The data results were obtained through direct observation to Dewi Kwan Im Palembang Temple, interviews with five sources, and literature studies. The conclusion of this research is the celebration rituals of Dewi Kwan Im at Dewi Kwan Im Palembang Temple is a form of respect and gratitude of Khonghucu people’s to Dewi Kwan Im for the blessings and help which recieved by the Khonghucu people’s during this time. Other than that the tradition which there at Dewi Kwan Im Palembang Temple is a combination of Hokkien culture society.Penelitian ini membahas upacara perayaan Dewi Kwan Im yaitu hari Dewi Kwan Im meninggalkan dunia. Dewi Kwan Im merupakan dewi yang sangat dihormati oleh umat Khonghucu sebab Dewi Kwan Im dipercaya dapat membantu umat Khonghucu yang membutuhkan pertolongan. Oleh karena itu umat Khonghucu selalu merayakan hari besar Dewi Kwan Im. Kelenteng Dewi Kwan Im yang berada di KM 12 Palembang turut mengadakan upacara perayaan dalam menyambut hari besar Dewi Kwan Im dengan memiliki tradisi upacara sendiri dalam melaksanakan upacara perayaan Dewi Kwan Im. Setiap prosesi upacara yang dilaksanakan di Kelenteng Dewi Kwan Im Palembang mempunyai makna di dalamnya. Tujuan penelitian ini adalah untuk mengetahui makna upacara perayaan Dewi Kwan Im yang dilaksanakan di Kelenteng Dewi Kwan Im Palembang dan untuk mengetahui tradisi yang dilakukan oleh umat Khonghucu di Kelenteng Dewi Kwan Im Palembang dalam merayakan upacara Dewi Kwan Im. Teori yang digunakan dalam penelitian ini yaitu teori semiotika, teori komunikasi transendental dan teori asimilasi. Metode penelitian yang digunakan adalah metode penelitian kualitatif dengan pendekatan studi kasus. Hasil data diperoleh melalui observasi langsung ke Kelenteng Dewi Kwan Im Palembang, wawancara dengan lima narasumber, dan studi kepustakaan. Kesimpulan dari penelitian ini adalah upacara perayaan Dewi Kwan Im yang dilaksanakan di Kelenteng Dewi Kwan Im Palembang merupakan bentuk rasa hormat dan terima kasih umat Khonghucu kepada Dewi Kwan Im atas berkat dan pertolongan yang diterima oleh umat Khonghucu selama ini. Selain itu tradisi yang ada di Kelenteng Dewi Kwan Im Palembang merupakan gabungan dari budaya masyarakat Hokkien.